2011
DOI: 10.1016/j.sleep.2010.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of restless legs syndrome in North American and Western European populations: A systematic review

Abstract: Background Restless legs syndrome (RLS) is a potentially debilitating sleep disorder that affects a significant percentage of North American and European adults. Although standardized RLS diagnostic criteria are now established and widely accepted, reported prevalence estimates have varied widely. In this paper, we review the literature regarding RLS prevalence in North American and Western European adult populations, examine potential sources of variation, briefly discuss the impact of RLS, and offer recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
129
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 84 publications
(279 reference statements)
14
129
4
1
Order By: Relevance
“…1,12,[33][34][35] Documented prevalence of RLS in primary care settings has typically averaged higher than that reported in population cohorts or random samples from the general population, possibly reflecting overall poorer health in primary care patients. 1 Primary care patients may also be more likely to seek medical care for conditions related to RLS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,12,[33][34][35] Documented prevalence of RLS in primary care settings has typically averaged higher than that reported in population cohorts or random samples from the general population, possibly reflecting overall poorer health in primary care patients. 1 Primary care patients may also be more likely to seek medical care for conditions related to RLS.…”
Section: Discussionmentioning
confidence: 99%
“…1,12,[33][34][35] Documented prevalence of RLS in primary care settings has typically averaged higher than that reported in population cohorts or random samples from the general population, possibly reflecting overall poorer health in primary care patients. 1 Primary care patients may also be more likely to seek medical care for conditions related to RLS. 1,39 The definition of clinically significant RLS has varied across studies, from no symptom frequency or severity requirement 36 to symptoms at least twice/week with at least moderate distress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Clinical and basic research demonstrated the necessity and importance of sleep to human health, [2][3][4][5][6][7][8] polysomnography moved from the laboratory to the clinic, 9,10 and epidemiological studies showed that sleep disorders were some of the most prevalent diseases known to mankind. [11][12][13] These advances fostered creation and development of organizations focused on clinical sleep medicine such as the American Academy of Sleep Medicine (AASM) and the American Board of Sleep Medicine (ABSM). These organizations appreciated the need for specialized training and certification to ensure physician competency in caring for patients with sleep disorders.…”
mentioning
confidence: 99%